Evaluation of PE/PP-GMA fabric for the Adsorption of Lead and Lithium Ions: A Study on Selectivity and Performance - Nergui, Otgonpurev (Scientific transaction of the National University of Mongolia. Physics, 2024)
The radiation-induced graft polymerization method is discussed. In this study, a PE/PP fabric was irradiated with a 10 kGy electron beam, followed by the grafting of glycidyl methacrylate (GMA) using a graft polymerization method to produce PE/PP-g-GMA fabric. The epoxy groups of the GMA grafted side chains were subsequently converted to sulfonate groups, forming PE/PP-g-GMA-Na₂SO₃. The physical and morphological properties of the adsorbent were analyzed using Fourier transform infrared spectroscopy (FT-IR) and Scanning electron microscopy (SEM). The PE/PP-g-GMA-Na₂SO₃ fabric demonstrated effective adsorption of lead (Pb²⁺,) and lithium (Li⁺) from solutions with concentrations of 100 ppb and 1 ppm in pure and mixed systems at different pH levels (3, 5, 7). The concentration of metal ions in the solutions was determined using Inductively Coupled plasma optical emission spectroscopy (ICP-OES) and Inductively coupled plasma mass spectrometry (ICP-MS), confirming the fabric’s adsorption efficiency. The experiment was crucial for enhancing fellows’ understanding of the practical and theoretical aspects of radiation-induced graft polymerization. This research was conducted at the Takasaki Institute for Advanced Quantum Science, QST in Takasaki , Japan.